Beszállítói termékek a magyar feldolgozóiparban - Békés Gábor; Muraközy Balázs (Hungarian Academy of Sciences, Institute of Economics, 2016)
– Global Value Chains play an increasing role in production and export in modern economies. Being part of such global chains can fundamentally affect the performance of a firm, a country, or an industry. In this study, we analyze the production and export of intermediate products and capital goods by Hungarian manufacturing firms, using firm-level production and export data. We show that such products account for two-thirds and three-fourths of production and exports, respectively. The share of such products is fundamentally determined by industry; therefore, an economic policy focusing on the appropriate industries can target potential suppliers quite effectively. By using regression analysis, we show that firms producing intemediate goods are more productive than their peers producing consumer goods, which is in line with the potential presence of knowledge spillovers.
Keywords: D22; D24; F14; L60; 330; suppliers; capital goods; manufacturing; export